Theoretical and Numerical Aspects of a Third-order Three-point Nonhomogeneous Boundary Value Problem - Martinez, André L. M.; Ferreira, Marcelo R. A.; Castelani, Emerson V. (Trends in Computational and Applied Mathematics, 2019)
In this paper we are considering a third-order three-point equation with nonhomogeneous conditions in the boundary. Using Krasnoselskii's Theorem and Leray-Schauder Alternative we provide existence results of positive solutions for this problem. Nontrivials examples are given and a numerical method is introduced.